Emotional void and identity fragmentation: madness and narcissism in “Lady Audley’s Secret” by Mary Elizabeth Braddon (1862). - Lantieri, Paolo (English Studies at NBU, 2025)
This research aims at investigating the psychological dimension of the protagonist Lady Audley on the grounds of the dialectic of alleged madness and assumed narcissistic personality disorder related to psychoanalytic literary methodology and criticism. In the light of the first Freudian studies of the first decade of the twentieth century and the subsequent outcomes, we attempt the hypothesis of female identity construction onto typically narcissistic features, in the perspective of Freud’s unconscious anticipated by Mary Elizabeth Braddon in her prose generating not only a sensation novel but also an innovative psychological plot depicting the double nature of Victorian society from the perspective of a woman labeled as insane.